Simian virus 40-transformed cells express new species of proteins precipitable by anti-simian virus 40 tumor serum. - Kress, M (1979)
In addition to the virus-coded large-T and small-t antigens, two new classes of proteins were immunoprecipitated by anti-simian virus 40 (SV40) tumor serum from extracts of various SV40-transformed cell lines. These were as follows: (i) proteins (termed "super-T proteins") with an Mr higher than that of large-T antigen (86,000), which were found in many SV40-transformed cell lines derived from mouse and rat cells (super-T proteins and large-T antigen appeared to have closely related structures as judged by the Chromobead elution patterns of their methionine-labeled tryptic peptides); (ii) proteins (termed "55K proteins") with an Mr ranging from 50,000 to 60,000, which were present in all SV40-transformed cell lines examined so far, including those obtained by chromosome-mediated gene transfer. The 55K proteins were not structurally related to large-T antigens, as judged by the Chromobead elution patterns of their methionine-labeled tryptic peptides. Our data are compatible with the assumption that the 55K proteins are largely or totally cell coded.